Perspektif Islamic Moral Economy (Ime) Terhadap Gig Economy: Tantangan Keadilan Dan Kesejahteraan Pekerja Di Era Digital - Sahida, Gayan Asykar; Bintang, Aldy Komara; Hayati, Aisyah Miratil (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2013)
The gig economy, which is rapidly growing in the digital era, offers flexibility and broader access to employment opportunities. However, this system also presents challenges to workers' welfare and fairness, including income instability, limited social security, and job insecurity. In the context of Islamic moral economy, the principles of justice (al-‘adl) and welfare (maslahah) are essential foundations for improving this system. The application of ijarah (leasing) and musyarakah (profit-sharing) contracts offers ethical solutions, ensuring contract clarity and providing worker protection. Through the integration of Islamic moral economy principles, the gig economy has the potential to become a system that supports social welfare, enhances worker justice, and creates a positive economic impact overall.   Gig economy, yang semakin berkembang di era digital, menawarkanfleksibilitas dan kesempatan akses kerja yang lebih luas. Namun, sistem inimembawa tantangan bagi kesejahteraan dan keadilan pekerja, sepertiketidakpastian pendapatan, minimnya jaminan sosial, dan risiko kehilanganpekerjaan. Dalam konteks ekonomi moral Islam, konsep keadilan (al-‘adl) dan kesejahteraan (maslahah) menjadi dasar penting untuk memperbaiki sistem ini. Penerapan akad ijarah (sewa-menyewa) dan musyarakah (kerjasama bagi hasil) menawarkan solusi yang etis, memastikan kejelasan kontrak, dan memberikanperlindungan bagi pekerja. Melalui integrasi prinsip ekonomi moral Islam, gig economy berpotensi menjadi sistem yang mendukung kesejahteraan sosial, meningkatkan keadilan bagi pekerja, dan menciptakan dampak positif bagiekonomi secara keseluruhan.